2022
DOI: 10.1177/07334648221104380
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Telephone-Based Cardiac Rehabilitation Services Delivered to Adults 65 and Older During the Early Months of the COVID-19 Pandemic

Abstract: This study was performed to evaluate the effectiveness of a hybrid, telephone-based cardiac rehabilitation (TBCR) program implemented early in the COVID-19 pandemic compared with in-person, center-based programming offered prior to the pandemic. The focus was on older adults’ engagement and outcomes. Matched groups of hybrid and in-person cardiac rehabilitation (CR) participants were created from existing data and compared using t-tests and repeated measures ANOVAs. Qualitative interviews were conducted with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
2
0
2
Order By: Relevance
“…This phase is characterized by the patient being no longer physically linked to the treatment centers but remotely. Ownbey et al 12 showed no significant differences in patient outcomes between hybrid and face-toface care, indicating that remote EBCR is a viable addition to face-to-face care. 12 However, in Brazil, as in other countries, 13 most healthcare professionals have little or no experience implementing home and remote RCBE; in addition, medical insurance and the unified health system (SUS) usually do not cover this type of care.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…This phase is characterized by the patient being no longer physically linked to the treatment centers but remotely. Ownbey et al 12 showed no significant differences in patient outcomes between hybrid and face-toface care, indicating that remote EBCR is a viable addition to face-to-face care. 12 However, in Brazil, as in other countries, 13 most healthcare professionals have little or no experience implementing home and remote RCBE; in addition, medical insurance and the unified health system (SUS) usually do not cover this type of care.…”
mentioning
confidence: 99%
“…Ownbey et al 12 showed no significant differences in patient outcomes between hybrid and face-toface care, indicating that remote EBCR is a viable addition to face-to-face care. 12 However, in Brazil, as in other countries, 13 most healthcare professionals have little or no experience implementing home and remote RCBE; in addition, medical insurance and the unified health system (SUS) usually do not cover this type of care. Greater investments are needed in training professionals and implementing remote exercise monitoring, education for healthy living, and behavior modification to improve overall health.…”
mentioning
confidence: 99%
See 2 more Smart Citations